#10: Tropism, Susceptibility, and Infectivity of Differentiated Human Tonsillar Epithelial Cells by Different Influenza Viruses. (28th June 2021) - Okda*, Faten A; Webby, Richard
Abstract: Introduction: Influenza viruses cause significant socioeconomic impact due to annual outbreaks and pandemic risks. Human tonsil epithelium cells (HTEC) are a heterogeneous group of actively differentiating epithelia comprising stratified squamous epithelium and reticulated crypt cells with abundant keratin expression. Hypothesis: We hypothesized that the tonsils are a primary site for influenza infection and sustained viral replication. Methods and Results: Primary HTEC (ScienCell Research Laboratories) were grown using an air-liquid interface and infected apically with different influenza viruses at various MOIs to measure viral growth kinetics. These cells were highly differentiated, with subpopulations of cells including ciliated, non-ciliated cells and specialized cells with secretory functions. There was a heterogenous distribution of both human-like (α2, 6-linked) and avian-like (α2, 3-linked) sialic acid receptors. The HTEC surface and crypts were lined with pseudostratified columnar ciliated cells possessing both α2, 6-linked and α2, 3-linked sialic acid receptors that were interrupted by patches of reticular epithelial cells. The HTEC epithelial cells were permissive for growth of influenza A and B viruses. A subset of cells, mostly ciliated cells, underwent apoptosis while others including non-ciliated cells remained intact despite being positive for influenza virus nucleoprotein. Interestingly, differences were seen between subtypes with colocalization of H3N2 virus and non-ciliated cells while H1N1 virus mostly associated with ciliated cells. Conclusion: Our results implicated human tonsillar crypt epithelium as a site for influenza virus replication. The tonsil epithelium cell culture differentiated system provides a valuable in vitro model for studying cellular tropism, infectivity, cytokines immune response and the pathogenesis of influenza viruses for better development of effective universal vaccine and therapies against different strains of influenza viruses.